The relationship between N isotopic fractionation within soybean and N2 fixation during soybean development. Issue 3 (22nd May 2014) - Schweiger, Peter; Hofer, Michaela; Vollmann, Johann; Wanek, Wolfgang
<x xml:space="preserve">Abstract</x> The contribution of N2 fixation to overall soybean N uptake has most commonly been quantified by N isotope‐based methods, which rely on isotopic differences in plant N between legumes and non‐fixing reference plants. The choice of non‐fixing reference plants is critical for the accuracy of isotope‐based methods, and mismatched reference plants remain a potential source of error. Accurate estimates of soybean N2 fixation also require information on N isotopic fractionation within soybean. On the basis of a previous observation of a close correlation between an expression of N fractionation within soybean and the proportion of plant N derived from atmosphere (%Ndfa) determined by 15N natural abundance, this field study aimed at assessing the relationship between various expressions describing intraplant 15N or N partitioning and %Ndfa during soybean development. Starting from a late vegetative stage until beginning senescence, the N content and N isotopic composition of shoots, roots and nodules of nodulated and non‐nodulated soybeans was determined at eight different developmental stages. Regression analysis showed that %Ndfa most closely correlated with the difference in the N isotopic composition of shoot N minus that of root including nodule N, and that this relationship was similar to that obtained in a previous multi‐site field study. We therefore consider this expression to hold promise as a means of quantifying %Ndfa independent of a reference plant, which would avoid some of the external sources of error introduced by the use of reference plants in determining %Ndfa.